Mortality In Thalassemic Patients From Solapur District, Maharashtra State, India - Nikam, S V; Dama, S B; Chondekar, RP; Dama, L B; Jawale, C S (Bangladesh Journal of Medical Science, 2012)
Objective: The aim of the present study is to surveying the mortality in thalassemic patients from Solapur District, Maharashtra State, India. Methods: Present observational survey study, one hundred twenty five clinically proved by their medical reports, cases of thalassemic children's with age 6 months to 18 Years, coming for to get blood transfusion from different parts of Solapur district. Results: The results indicates that the increased mortality during 11-15 years of age. As a result, transfusional iron overload can cause increased morbidity and premature mortality in thalassemia patients. This study will be helpful in further defining the morbidity and mortality in thalassemic patients. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11717 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12